The Genre of an Essay by Andrej Mráz in the Context of the Slovak-Vojvodina Interconnections - Marína Šimáková Speváková (Slovenska Literatura, 2017)
The paper deals with the aspects of the genre of the essay titled Rozhovory o juhoslovanských Slovákoch /Dialogues about Yugoslavian Slovaks/ by Andrej Mráz in the context of research into literature written in the interwar period. The goal of the paper is to present the invariant elements and the special features of Mráz´s essay as well as to show how inspiring it is in the present. The paper builds on the fundamental studies on essay as a genre by A. Bagin, R. Chmel, P. Valček, M. Horváth as well as the assessment of Andrej Mráz´s literary work by A. Matuška, K. Rosenubaum, V. Petrík, O. Čepan. Mráz´s essay deserves attention in the context of updating the inter-literary dialogue between Slovakia and Yugoslavia, i.e. Vojvodina. In relation to that the paper shows the special features of Mráz´s genre form within the history of the genre in Slovakia. The essay-like elements are also contained in less extensive articles by A. Mráz dedicated to the subject. The bibliography of the works by Andrej Mráz compiled in 1964 is extended by a list of his writings published in Yugoslavian magazines. The essay is considered to be inspiring in the context of developing the Slovak – Vojvodina inter-literary relations. What is also stimulating is Mráz´s critical attitude to the efforts to gain a more objective understanding of ourselves and the others.